Butterflies of Nanda Devi National Park - a World Heritage Site - Uniyal, V. P. (Indian Forester, 2004)
Nanda Devi National Park, declared as such in 1982, was further made a Biosphere Reserve in January 1988. Realising its biological diversity and several rare and endangered endemic floral and faunal species, it was decalred a world heritage site by the United Nations in Dec. 1988. This research supports many plant and faunal spices. The author has documented 35 butterfly species belonging to 25 genera and four families, as a result of his study between in 2001, in this Park, as part of the Garhwal Rifles Regimental Centre Lansdowne expedition in this region.